2021
DOI: 10.1096/fj.202002185rr
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microchimerism and cell‐mediated immune‐modulation enhance engraftment following semi‐allogenic intrauterine transplantation

Abstract: Successful intrauterine hematopoietic cell transplantation (IUT) for congenital hemoglobinopathies is hampered by maternal alloresponsiveness. We investigate these interactions in semi‐allogenic murine IUT. E14 fetuses (B6 females × BALB/c males) were each treated with 5E+6 maternal (B6) or paternal (BALB/c) bone marrow cells and serially monitored for chimerism (>1% engraftment), trafficked maternal immune cells, and immune responsiveness to donor cells. A total of 41.0% of maternal IUT recipients (mIUT) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 68 publications
(203 reference statements)
3
18
0
Order By: Relevance
“…Unique maternal and recipient TCR/BCR repertoires may serve as therapeutic targets to improve transplantation outcomes. This clinically relevant data, similar to our previous study, 16 supports paternal IUT for clinical trials and encourages short-term maternal immune suppression at IUT.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Unique maternal and recipient TCR/BCR repertoires may serve as therapeutic targets to improve transplantation outcomes. This clinically relevant data, similar to our previous study, 16 supports paternal IUT for clinical trials and encourages short-term maternal immune suppression at IUT.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to other reported models using maternal donor cells, 30,31 the model for IUT clinical trial NCT02986698, we observed microchimerism post-mIUT despite reduced MMc, similar to our earlier work. 16 Thus, DCC appears primarily dependent on cell origin, not MMc. We demonstrated that maternal cell trafficking is an active process, the quality of which appears to influence the fetal recipient's immune response to donor cells.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations